Artificial Intelligence as a Learning Assistant: Child with Intellectual Disability Distinguish the Letters B and D - Sumartini; Budi Susetyo; Iding Tarsidi (Universitas Pendidikan Ganesha, 2026)
Inclusive education requires learning services that are able to accommodate the needs of all students, including students with intellectual disabilities. One of the common problems experienced by students with intellectual disabilities is difficulty distinguishing the letters b and d due to the visual similarity between the two letters. This condition affects students’ basic literacy skills, particularly in reading and writing. The use of Artificial Intelligence (AI) in learning is considered to have the potential to create more adaptive, interactive, and student-centered learning media for students with special needs. This study aimed to analyze the effectiveness of AI-based learning media in improving students’ ability to distinguish the letters b and d. The study employed a Research and Development (R&D) approach using the ADDIE model. The research subjects consisted of five fifth-grade students with intellectual disabilities. Data were collected through observations, interviews, literacy tests, and documentation. The research instruments included student engagement observation sheets, interview guidelines, and pre-test and post-test questions. Data were analyzed using descriptive quantitative and qualitative techniques by comparing students’ abilities before and after the implementation of AI-based learning media. The findings revealed an improvement in students’ ability to recognize and write the letters b and d, indicated by an average score increase of 30% from pre-test to post-test. In addition, students demonstrated higher motivation, participation, and engagement during the learning process. This study concludes that AI-based learning media are effective in supporting the development of basic literacy skills among students with intellectual disabilities and have implications for the implementation of more adaptive and interactive inclusive learning practices.